A new concept of ceramic consumable anode for iron pyroelectrolysis in magnesium aluminosilicate melts. Issue 9 (July 2016) - Ferreira, Nuno M.; Kovalevsky, Andrei V.; Ferro, Marta C.; Costa, Florinda M.; Frade, Jorge R.
Abstract: Driven by environmental challenges and global movement to carbon-lean technologies, the pyroelectrolysis process for iron extraction from oxide melts is being proposed as an interesting alternative to the traditional steelmaking. Still, one of the critical issues impacting the prospects of this technology includes the development of appropriate anode materials, taking into account the extremely aggressive nature of oxide melts at very high temperatures. Here we propose a unique concept of consumable anode for pyroelectrolysis process, based on multicomponent ferrospinel-based ceramics. The electrochemical studies and post-mortem XRD/SEM/EDS analysis of the electrolysis cells have demonstrated that ceramic spinel anodes can sustain significant current densities for making the process feasible, while their consumption by interaction with Si-containing species from the molten electrolyte was found to be moderate.